Monotherapy for the Treatment of Lymphedema in Children: A Review - de Godoy, Ana Carolina P.; de Godoy, Jose Maria Pereira; Guerreiro Godoy, Maria de Fatima (Current Pediatric Reviews, 2022)
The Godoy Method of cervical lymphatic therapy is the first treatment option as monotherapy for children which facilitates achieving normalization or near normalization of the affected limb as well as the maintenance of the results, which could assist millions of children throughout the world.
Keywords: edema